2019
DOI: 10.1039/c8nr10468a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal energy transport across the graphene/h-BN heterostructure interface

Abstract: Interface topography has great impact on thermal energy transport across the GR/h-BN heterostructure interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…A similar effect of the temperature elevation on Kaptiza resistance was observed for graphene-boron nitride hetero-nanosheets in the works done by Eshkalak et al . 47 and Liu et al 48 .
Figure 7 The changes in Kapitza thermal resistance of six constructed grain boundaries A 1 (5–7–6–6–s), A 2 (5–7–6–s), A 3 (5–7–5–7–s), A 4 (5–7–6–6–a), A 5 (5–7–6–a), and A 6 (5–7–5–7–a) in BC 3 GrHs as a function of temperature at ΔT = 40 K and zero strain.
…”
Section: Resultsmentioning
confidence: 96%
“…A similar effect of the temperature elevation on Kaptiza resistance was observed for graphene-boron nitride hetero-nanosheets in the works done by Eshkalak et al . 47 and Liu et al 48 .
Figure 7 The changes in Kapitza thermal resistance of six constructed grain boundaries A 1 (5–7–6–6–s), A 2 (5–7–6–s), A 3 (5–7–5–7–s), A 4 (5–7–6–6–a), A 5 (5–7–6–a), and A 6 (5–7–5–7–a) in BC 3 GrHs as a function of temperature at ΔT = 40 K and zero strain.
…”
Section: Resultsmentioning
confidence: 96%
“…Relatively, Chen et al 31 , 32 found that the in-plane Gr/h-BN heterostructure exhibits a negative differential thermal resistance behavior, which is caused by the phonon resonance effect and the lattice vibration mismatch. In addition, topological defects, 7 doping and interface topography optimization 33 were employed to effectively improve the thermal energy transport across the in-plane Gr/h-BN heterostructure interface. These previous studies have enriched our understanding of the interfacial thermal transport properties of Gr/h-BN heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the zigzag interfaces with either boron–carbon or nitrogen–carbon links have smaller formation energy values than that of the armchair interface, the former is more likely formed. Researchers have mostly focused on the heat transfer of graphene/h-BN in-plane heterostructures with zigzag interfaces [ 24 , 25 , 26 ]. However, the graphene/h-BN in-plane heterostructures with armchair interfaces have also been prepared in experiments [ 15 ], and they show a higher bandgap as compared to the pristine nanoribbons [ 17 , 27 ].…”
Section: Methodsmentioning
confidence: 99%